Effect of the underwater torque on the energy cost, drag and efficiency of front crawl swimming - Zamparo, P.; Capelli, C.; Termin, B.; Pendergast, D. R.; Di Prampero, P. E. (European Journal of Applied Physiology, 1996)
Underwater torque (T') is defined as the product of the force with which the swimmer's feet tend to sink times the distance between the feet and the centre of volume of the lungs. It has previously been shown that experimental changes of T', obtained by securing around the swimmer's waist a plastic tube filled, on different occasions, with air, water or 2-kg lead, were accompanied by changes in the energy cost of swimming per unit of distance (Cs) at any given speed. The aim of this study was to investigate whether the observed increases of Cs with T' during front crawl swimming were due to an increase of active body drag (Db), a decrease of drag efficiency (eta /d) or both. The effect of experimental changes of T' on Cs, Db and eta /d were therefore studied on a group of eight male elite swimmers at two submaximal speeds (1.00 and 1.23 m.s-1). To compare different subjects and different speeds, the individual data for Cs, Db, eta /d and T' were normalized dividing them by the corresponding individual averages. These were calculated from all individual data (of Cs, Db, eta /d and T') obtained from that subject at that speed. It was found that, between the two extremes of this study (tube filled with air and with 2-kg lead), T' increased by 73% and that Cs, Db and eta /d increased linearly with T'. The increase of Cs between the two extremes was intermediate (approximately 20%) between that of Db (approximately 35%) and of eta /d (approximately 16%). Thus, the actual strategy implemented by the swimmers to counteract T', was to tolerate a large increase of Db. This led also to a substantial (albeit smaller) increase of r/d, the effect of which was to reduce the increase of Cs that would otherwise have occurred.